Problematika Disabilitas Dalam Mengikuti Perkuliahan - Abadi, Sugeng; Yaum, Lailil Aflakhul; Prystiananta, Nostalgianti Citra (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to identify the various obstacles faced by students with disabilities in participating in academic activities in the lectures. The method used is descriptive qualitative Husserl. In selection of participants using purposive sampling with the criteria of students with UNIPAR students with disabilities, and 117 participants were obtained. Collecting data collection using semi-structured interviews, observation, and documentation using triangulation techniques. Using data analysis using triagulation techniques. The results of the study obtained there are problems in the form of challenges or obstacles faced by students with disabilities in attending lectures from disabilities in attending lectures from internal and external parties, namely students themselves, from the lecturers, and infrastructure that needs to be improved. Accessibility needs to be improved. However, there are policies policies provided by the campus include Lecture Implementation Policy, the existence of the PSLD Unit and the DGCC Unit, there is training for lecturers and academic community. lecturers and academic community, prioritizing inclusive education and gender equality to create a friendly and inclusive campus. gender equality to create a friendly and inclusive campus.